Exploring a two-layer green supply chain game theoretic model with credit linked demand and mark-up under revenue sharing contract. (20th March 2020) - Panja, Subrata; Mondal, Shyamal Kumar
Abstract: In this paper, a two-layer green supply chain has been considered consisting of a manufacturer and a retailer. Also in this study two game theoretic models have been analyzed where, in the first model the market demand depends on green degree of the produced products and selling price of the retailer, whereas for second model, demand depends not only on green degree and selling price of the retailer but also on the credit period, offered by the retailer to the customers. Here, the manufacturer produces green products and his/her production cost depends on green degree of the products and after that s/he wholesales the products on a mark-up based on his/her production cost, while the retailer decides his/her mark-up based on manufacturer's wholesale price for Model I and for Model II s/he decides the mark-up on the basis of both wholesale price and the credit period. All models have been solved by considering three decision scenarios as centralized, decentralized and revenue sharing contract. Under revenue sharing contract, through numerical investigations we reveal that not only Model II gives better profit structure for both manufacturer and retailer compared to Model I but also for Model II a win-win situation can be achieved, though the contract is unable to improve the green degree of the product. We have also analyzed, how retailer can improve his/her individual profit structure along with other supply chain members by offering credit period. Finally, sensitivity analysis has been performed with respect to some key demand sensitivity parameters and retailer's interest loss rate due to offered credit period to make important insights on several optimal decisions. Highlights: Two-layer manufacturer-retailer GSC model has been developed. . Green degree dependent production cost has been considered in a GSC model. . Credit sensitive demand has been structured in a GSC model. . Effects of offering credit period on win-win situation has been analyzed. . Revenue sharing contract has been used as the contract mechanism.